2017
DOI: 10.1002/jlb.4mr0717-277r
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis: Rewiring host cell signaling to promote infection

Abstract: The ability of Mycobacterium tuberculosis to cause disease hinges upon successfully thwarting the innate defenses of the macrophage host cell. The pathogen's trump card is its armory of virulence factors that throw normal host cell signaling into disarray. This process of subverting the macrophage begins upon entry into the cell, when M. tuberculosis actively inhibits the fusion of the bacilli-laden phagosomes with lysosomes. The pathogen then modulates an array of host signal transduction pathways, which damp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 88 publications
(202 reference statements)
1
40
0
Order By: Relevance
“…In line with this, there is also evidence that mycobacteria inhibit pyroptosis of infected macrophages via diverse mechanisms (53). However, recent studies found that lytic cell death (pyroptosis and necrosis/necroptosis) helps mycobacteria to evade host immunity and disseminate the infection (25,54). Indeed, in the present study we found that pyroptotic cell death promotes the expansion of mycobacteria in Dram1-deficient zebrafish hosts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with this, there is also evidence that mycobacteria inhibit pyroptosis of infected macrophages via diverse mechanisms (53). However, recent studies found that lytic cell death (pyroptosis and necrosis/necroptosis) helps mycobacteria to evade host immunity and disseminate the infection (25,54). Indeed, in the present study we found that pyroptotic cell death promotes the expansion of mycobacteria in Dram1-deficient zebrafish hosts.…”
Section: Discussionsupporting
confidence: 88%
“…Apoptosis of infected cells is generally regarded as a host-protective defence mechanism against mycobacterial infection, and virulent Mtb therefore actively inhibit apoptosis (20,22,23). In contrast, necroptosis and pyroptosis are lytic forms of cell death that create an inflammatory environment that may facilitate extracellular growth and disease progression (24,25).…”
mentioning
confidence: 99%
“…In addition, macrophages generate nitric oxide and reactive oxygen species, T-cells, and natural killer (NK) cells [36, 37]. In the context of obesity-related diabetes, increased pro-inflammatory cytokines, reactive oxygen species, and nitric oxide cause insulin resistance through a cascade of inflammation pathways leading to hyperglycemia [38–40].…”
Section: Section 2: Pathophysiology Of Tb Disease and Stress Hyperglymentioning
confidence: 99%
“…Disease-causing mycobacteria, however, can persist and replicate within alveolar macrophages via a bewildering range of evolved mechanisms that subvert and interfere with host immune responses (de Chastellier, 2009;Cambier et al, 2014;Schorey and Schlesinger, 2016;Awuh and Flo, 2017). These mechanisms include recruitment of cell surface receptors on the host macrophage; blocking of macrophage phagosome-lysosome fusion; detoxification of reactive oxygen and nitrogen intermediates (ROI and RNI); harnessing of intracellular nutrient supply and metabolism; inhibition of apoptosis and autophagy; suppression of antigen presentation; modulation of macrophage signalling pathways; cytosolic escape from the phagosome; and induction of necrosis, which leads to immunopathology and shedding of the pathogen from the host (Ehrt and Schnappinger, 2009;Hussain Bhat and Mukhopadhyay, 2015;Queval et al, 2017;BoseDasgupta and Pieters, 2018;Chaurasiya, 2018;Stutz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%